Desain Sistem Informasi Tri Dharma Perguruan Tinggi Univesitas Hamzanwadi - Jamaluddin Jamaluddin; Baiq Desi Dwi Arianti; Baiq Aryani Novianti; Maman Asrobi (Fakultas Teknik Universitas Hamzanwadi, 2022)
The Tri Dharma is three obligations that exist in higher education. The three obligations include education or teaching, research, and community service. Each component of higher education, especially the academic community, is responsible for realizing and implementing the Tri Dharma of Higher Education. Each component of the obligation in the Tri Dharma of higher education must be equipped with various physical evidence, such as documents, learning media, etc. Every University in Indonesia must have a system that can record all evidence of the implementation of the Tri Dharma. Therefore, this study aims to develop software that can help Hamzanwadi University record every progress of the three Tri Dharma components of higher education that the academic community has carried out at Hamzanwadi University, especially Lecturers. The development model used in this study is the Waterfall Development model (Requirements Analysis, Design, Development, Testing, Maintenance), but this study only describes the Design stage. The results obtained are in the form of system requirements, client needs, system architecture, flowcharts, and DFD of the designed system